Rifugiati I moriscos e l'Italia - Pomara, Bruno (Premio Istituto Sangalli per la storia religiosa, 2017)
The book brings to light a little-known story: the arrival in Italy of thousands of Moriscos exiles, descendants of Arab-Muslim origin, settled for centuries in the Iberian peninsula, baptized following the Christian Reconquista (1492), often accused of crypto-Islamism and betrayal of the homeland, eventually expelled and deported from Spain (1609-1614). What are the obstacles encountered by refugees along the journey of their exodus? What is the behavior of the authorities with respect to the landings? And in what terms have the refugees interacted with the local populations? These are current questions to ancient problems that Italy, in its political fragmentation, has already experienced.